2021
DOI: 10.33546/bnj.1521
|View full text |Cite
|
Sign up to set email alerts
|

Effect of care for child development training on cadres’ knowledge, attitude, and efficacy in Yogyakarta, Indonesia

Abstract: Background: Stunting is a common malnutrition problem among children in the world. The Care for Children Development (CCD) intervention is a strategy to reduce stunting. Objective: This study aimed to identify the effect of culturally modified CCD training on the knowledge, attitude, and efficacy (KAE) of cadres about stunting in the community.Methods: We conducted a community-based study with a quasi-experimental research design using a comparison group. The study was conducted from March 2018 to February 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 23 publications
(28 reference statements)
1
10
0
Order By: Relevance
“…Others made substantive modifications by providing more specific recommendations on how to engage in responsive play and communication activities and creating a structured curriculum to guide delivery agents in their interactions with caregivers. For example, seven studies explicitly reported making substantive modifications to the play and communication activities of the CCD package (( 24 ) [Indonesia]; ( 25 ) [Mozambique], ( 26 ) [Tanzania]; ( 27 ) [Malawi]; ( 28 ) [Kenya]; ( 29 ) [India and Pakistan]; ( 17 ) [Pakistan] 5 ). In Malawi, this consisted of modifying play and communication activities to focus on touch, hearing, and other senses for children with visual impairments ( 27 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Others made substantive modifications by providing more specific recommendations on how to engage in responsive play and communication activities and creating a structured curriculum to guide delivery agents in their interactions with caregivers. For example, seven studies explicitly reported making substantive modifications to the play and communication activities of the CCD package (( 24 ) [Indonesia]; ( 25 ) [Mozambique], ( 26 ) [Tanzania]; ( 27 ) [Malawi]; ( 28 ) [Kenya]; ( 29 ) [India and Pakistan]; ( 17 ) [Pakistan] 5 ). In Malawi, this consisted of modifying play and communication activities to focus on touch, hearing, and other senses for children with visual impairments ( 27 ).…”
Section: Resultsmentioning
confidence: 99%
“…For example, some caregivers stated that they would have liked a better explanation of the service's purpose (( 48 ) [Mozambique]) and to have more explicit and repetitive messages on why specific activities are important for children's development (( 43 ) [Malawi]). Two of the reports (( 24 ) [Indonesia]; ( 30 ) [Turkey]) described the training of delivery agents in the CCD package and one of them reported data on delivery agents' program acceptance. General practitioners and nurse-midwives in Turkey appreciated the content and materials of the CCD package and felt that the training improved their ability to engage caregivers in ECD counseling ( 30 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tadesse et al (2023) showed that maternal education was an important predictor for narrowing the urban rural disparities in childhood stunting. Knowledge of stunted mother need to improve with demonstrations and role plays demonstrated by Akhmadi et al, (2021) .…”
Section: Characteristics Based On Having Received Health Informationmentioning
confidence: 99%
“…19 and its health reasons based on the ICD-10 diagnosis code. The increasing number of patients' visits in the years 2021 and 2022 compared to 2020 might be affected by patients' decision to avoid healthcare during the beginning period of the pandemic.…”
mentioning
confidence: 99%